Road transportation is associated with decreased intestinal motility in horses - Raidal, Sharanne L.; Freccero, Francesca; Carstens, Ann; Weaver, Sarah; Padalino, Barbara (Frontiers in Veterinary Science, 2025)
BackgroundTransportation of horses has been associated with colic and changes to the gastrointestinal microbiome. Percutaneous abdominal ultrasonography using wireless, point-of-care transducers can be used to assess gastrointestinal motility in field settings.ObjectivesCharacterization of intestinal motility and salivary cortisol responses of horses completing commercial transportation of 10-12h.Study designProspective observational study of 30 horses with diverse signalment and transport histories. Clinical parameters, sonographic assessment of intestinal motility and saliva samples, were collected before departure (Tpre or T0), after off-loading (T1) and 2h after arrival (T2).ResultsAfter transportation, intestinal motility grades were reduced [Tpre median (IQR) composite motility grade: 8 (7-10), T1: 6 (4-7), T2: 7 (6-7); p < 0.001] and qualitative changes were observed in small intestinal sonographic appearance. High ambient temperatures during transport were associated with reduced intestinal motility at T1 (composite motility grade vs arrival temperature rs −0.45, p = 0.017) and T2 (cecal motility grade vs arrival temperature rs −0.74, p < 0.001). Horses with high heart rates, high sweat scores or abnormal demeanour on arrival demonstrated decreased intestinal motility. Salivary cortisol concentrations increased after transportation (mean difference, 95% CI, for T0 vs T1 was 1.66, 1.09−2.53 nmol/L) and were inversely associated with intestinal motility. Signalment and past travel history were not predictive of intestinal motility, but horses with unknown or no prior travel history (mean 12.8, 95%CI 8.2-17.4 nmol/L) had higher cortisol concentrations prior to departure than horses known to have travelled previously (7.9, 5.8−9.9 nmol/L, p = 0.023).ConclusionsThese findings suggest that transportation is associated with transient reductions in intestinal motility, particularly during hot ambient conditions and in horses with increased cortisol response. Possible effects of provision of water and food during transport warrant further investigation.